Mini-Implants in the Anchorage Armamentarium: New Paradigms in the Orthodontics - Masaru Yamaguchi; Toshihiro Inami; Ko Ito; Kazutaka Kasai; Yasuhiro Tanimoto (International Journal of Biomaterials)
Paradigms have started to shift in the orthodontic world since the introduction of mini-implants in the anchorage armamentarium. Various forms of skeletal anchorage, including miniscrews and miniplates, have been reported in the literature. Recently, great emphasis has been placed on the miniscrew type of temporary anchorage device (TAD). These devices are small, are implanted with a relatively simple surgical procedure, and increase the potential for better orthodontic results. Therefore, miniscrews not only free orthodontists from anchorage-demanding cases, but they also enable clinicians to have good control over tooth movement in 3 dimensions. The miniplate type also produces significant improvements in treatment outcomes and has widened the spectrum of orthodontics. The purpose of this paper is to update clinicians on the current concepts and versatile uses and clinical applications of skeletal anchorage in orthodontics.